The service sector revolution in India: A quantitative analysis - Rubina Verma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Following the economic liberalization in India, the service sector has gained prominence in the economy as it accounts for the largest share of GDP and, also that the share of this sector in GDP has been growing very rapidly. Empirical data reveal two significant trends in the service sector following liberalization in 1991: growth in service sector productivity and growth in services' trade. The objective of this paper is to build a simple three sector quantitative model which can capture the increase in the share of service sector in GDP after liberalization. Within the context of the model, there are two exogenous changes that occur across the two steady states years, 1980 and 1999: growth in sectoral total factor productivity (TFP) and increase in the level of trade in industrial and service sectors. The results from a counterfactual experiment reveal that shutting down sectoral TFP affects the ability of the model to capture the data trends whereas the absence of sectoral trade negligibly affects the results. Hence I conclude that services' productivity growth versus the increase in services' trade can better explain the value added growth observed in the Indian service sector across the two steady states.
Keywords: O14; O41; O53; 330; growth; trade; total factor productivity; services; India; Dienstleistungssektor; Deregulierung; Indien